Selection of 3D printing technology at SE “Ivchenko-Progress” application - Oleksandr Podobnyi; Mykhaylo Alyeynikov (Авіаційно-космічна техніка та технологія, 2024)
Currently, 3D printing technology is widespread throughout the world. This relates to the wide theoretical resources of this technology for manufacturing irregularly shaped parts with high precision from different steels and alloys, plastics, and ceramics with much lesser production time for parts with 3D printing than parts manufacturing using regular technologies. The wide technological and engineering resources of 3D printing give the possibility for permanently new parts development and testing, as well as the search for new types of equipment and materials that allow irregularly shaped parts from different materials. This article analyses the general subjects of 3D printing applications in industrial enterprises. Described the experience of this technology application in the manufacturing of different parts of aviation engines produced from metal, ceramic, and plastic materials. Given the results of research on metallurgical models and completed parts, information about the accuracy and quality of completed surfaces performed using 3D printing. Perform review and research of blanks and parts 3D printer manufactured: parts (bars, supports, conformatores) from ceramic materials; models from metal materials (metal-oxide dispersion-hardened titanium aluminum and heat-resistant alloys, heat-resistant alloy Inconel 718, titanium alloy Ti6Al4V (BT6 analogue), aluminium alloys AlSi and AlMg (composition close to АЛ2 and AЛ5), aluminium alloy AlMg5 (АМг5 analogue), heat-resistant nickel alloy ЭП648 (ВХ4Л), heat-resistant alloy ЖС32-ВИ); parts from plastic materials (impellers, flanges, T-branch) using burned-out models. The models and parts research obey the engineering specifications of the design drawings are given. Research contains models and parts’ physical and chemical properties analyses, their mechanical properties, ratings after heat treatment, as well as materials’ micro- and macrostructure analyses during different steps of parts manufacturing. Single shown results for parts manufactured after 3D printing using burned-out models: cast strength, model burn-out quality, remaining ash and other detrimental impurities, and cast roughness.